2017
DOI: 10.3389/fpsyg.2017.00635
|View full text |Cite
|
Sign up to set email alerts
|

Modernizing Relationship Therapy through Social Thermoregulation Theory: Evidence, Hypotheses, and Explorations

Abstract: In the present article the authors propose to modernize relationship therapy by integrating novel sensor and actuator technologies that can help optimize people’s thermoregulation, especially as they pertain to social contexts. Specifically, they propose to integrate Social Thermoregulation Theory ( IJzerman et al., 2015a ; IJzerman and Hogerzeil, 2017 ) into Emotionally Focused Therapy by first doing exploratory research during couples’ ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Indeed, one study provides intriguing evidence that a single session of mild, short-duration hyperthermia reduced depressive symptoms among participants with clinical depression (Janssen et al, 2016). Other researchers have theorized that relationship quality might be enhanced by warm temperatures (IJzerman, Heine, Nagel, & Pronk, 2017). Our work is consistent with such theories, and with evidence that holding the hand of a close relationship partner can reduce threat-related distress (Coan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one study provides intriguing evidence that a single session of mild, short-duration hyperthermia reduced depressive symptoms among participants with clinical depression (Janssen et al, 2016). Other researchers have theorized that relationship quality might be enhanced by warm temperatures (IJzerman, Heine, Nagel, & Pronk, 2017). Our work is consistent with such theories, and with evidence that holding the hand of a close relationship partner can reduce threat-related distress (Coan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In adults, Wagemans and IJzerman (2014) found that people respond with peripheral temperature increases when seeing their sad partner, arguably to co-regulate their partner. The relationship literature is further replete with suggestions that people physiologically co-regulate in the service of homeostasis, which we have argued to include temperature homeostasis (IJzerman, Heine, et al, 2017). From this perspective, temperature regulation has become implicated in attachment processes, which, in turn, form the basis for how people form predictions about others.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the function and meaning associated with the transitional object developed and deepened to provide both safe haven and secure base functions, that is, facilitate soothing but also stimulating the courage to begin to explore. The above example demonstrates how transitional object usage can draw on and integrate ideas from attachment theory (Bowlby, 1988;Feeney & Collins, 2015;Mikulincer & Shaver, 2007), social thermoregulation theory (IJzerman et al, 2015;Ijzerman, Heine, Nagel, & Pronk, 2017), social touch (Maratos et al, 2017;Morrison, 2016;Uvn€ as-Moberg, Handlin, & Petersson, 2015), and huggable communication mediums (Nakanishi, Sumioka, & Ishiguro, 2016;Takahashi et al, 2017). Furthermore, this links back to Harlow's (1958) work with infant monkeys in discovering the importance of soft tactile sensations accompanied by (physical) warmth in imparting the emotional security (i.e., safeness) to explore (Harlow & Suomi, 1970).…”
Section: Cft For People With Attachment Traumamentioning
confidence: 82%